Implementasi Pembelajaran Berdiferensiasi Dalam Meningkatkan Aktivitas Belajar Siswa Kelas Tinggi di Sekolah Dasar Negeri 10 Pangkalpinang - Lestari Lestari; Hadarah Hadarah; Soleha Soleha (EDOIS: Journal of Islamic Education, 2023)
The purpose of this research is to obtain systematic, authentic, and accurate information about the facts related to the application of differentiated learning to increase student activity at State Elementary School 10 Pangkalpinang and efforts to overcome obstacles to differentiated learning. This research is qualitative with a phenomenological approach. The research subjects were the principal, teachers, library staff, and students at SDN 10 Pangkalpinang. The researcher used both primary and secondary data. Data collection methods include observation, interviews, and documentation. In this study, researchers used the Miles and Huberman model data analysis procedure. The data obtained were analyzed through the stages of data reduction, data presentation, and verification. Based on the results of the study, it can be concluded that (a) students are more active and involved in the learning process, which is reflected in their participation in discussions, questions, and group work. (b) Different teaching methods in differentiated learning, such as presenting content with videos, projects, or creative assignments, can positively affect students' learning activities. (c) Efforts to overcome obstacles include involving class associations, alumni, and companies to help implement an activity, providing training to teachers to better understand differentiated teaching strategies, and providing additional time to students who need help. This research is very important for educators and education policymakers to consider the importance of implementing differentiated learning strategies in an effort to improve the quality of education at a higher level. It also highlights the need for teacher training in implementing this approach effectively so that it can provide maximum benefits for all students in the higher grades.